A review of hetero-structured Ni-based active catalysts for urea electrolysis. Issue 17 (20th April 2022) - Li, Jiaxin; Wang, Shuli; Sun, Sijia; Wu, Xiang; Zhang, Baogang; Feng, Ligang
Abstract : Hetero-structured Ni-based active catalysts for urea electrolysis were reviewed, and challenges were faced for the integration of the components to fully make use of their strengths and make up for each other's weaknesses. Abstract : Urea electrooxidation has received considerable attention because of its tremendous practical application in environmental protection and energy regeneration. The catalytic performance of urea oxidation as an electrochemical reaction is highly determined by catalysts, and Ni-based catalysts have been intensively studied due to their low cost, facile structure tuning, and easy active phase formation based on the electrochemical-chemical mechanism. The Ni catalyst for urea oxidation can be largely improved by rational surface/interface structure optimization via various surface engineering approaches that provide more active sites, desirable crystal phase, and defects promoting the mass and electron transfer for the catalytic reaction. Due to significant recent advances, herein, we review the recent advances of heterostructured Ni-based active catalysts for urea electrolysis. The concerns about general heterostructured catalyst engineering principles in terms of crystal phase orientation, increased bond polarity, high-valent Ni formation, increased active surface area, electronic effect, and ensemble effect are first presented, and then theoretical analysis for the promotion effect is briefly demonstrated. Following this, specific hetero-structured Ni-based catalysts classified according to hetero-element doping, hetero-metallic alloying, and multi-component heterostructure construction are mainly discussed and analyzed with some typical examples. Finally, we present the problems, challenges, and perspective comments for the subject topic. It is noted that each component has its functionality to contribute to catalytic reactions, and the study on rationally integrated components to fully make use of their strengths and make up for each other's weaknesses is still a great challenge. Hopefully, this review could be helpful and instructive for the literature survey of heterostructured Ni-based catalysts in urea electrolysis.